Treatment of avulsed teeth with Emdogain((R)) - a case report - (:unkn) unknown (BLACKWELL MUNKSGAARD, 2005)
The present case report describes the reimplantation of avulsed teeth with the treatment of Emdogain((R)). Case was avulsed right maxillary permanent central and lateral incisor in a 9-year-old girl suffering from a traumatic injury. After pretreatment of avulsed teeth, Emdogain((R)) was applied to the root surface and into the extraction socket with subsequent replantation of the tooth. Evaluation parameters included horizontal and vertical percussion sound and periapical radiographs. At 1-2-6-12-month follow-up period, the clinical and radiographic appearance of the teeth showed resolution of mobility and no signs of replacement resorbption.
Keywords: Emdogain((R)); avulsed teeth; reimplantation; MATRIX DERIVATIVE EMDOGAIN(R); PERMANENT INCISORS; REPLANTATION; VIASPAN; DOGS; MILK